Book Review: La colonización del pasado: el imaginario occidental en las crónicas de Alvarado Tezozómoc, by José Pantoja Reyes - Atilano Gutiérrez, José Enrique (2023)
This paper is a critical commentary on the book by José Pantoja Reyes published in 2017 by Colofón publishing house (Mexico). In this way, what is intended is to discuss the theses, objectives and explanations that the author provides throughout his historiographical reading of the Mexicayótl and Mexicana chronicles of the indigenous historian Hernando de Alvarado Tezozómoc (1520/30 ca-1610). Specifically, we will address those issues that have to do with the weight of the western Indian discourse, the late medieval imaginary in the rhetorical writing of the second half of the sixteenth century and the contemporary interpretative horizon of the Indian chronicles.